2014
DOI: 10.5424/sjar/2014121-4299
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for litter size in Black Slavonian pigs

Abstract: The objective of this study was to estimate genetic parameters for litter size of Black Slavonian pigs using the repeatability, multiple trait, and random regression models, and to consider the possibility to increase litter size in Black Slavonian pigs by selection. A total of 4,733 litter records from the first to the sixth parity from sows that farrowed between January 1998 and December 2010 were included in the analysis. Individual record consisted of the following variables: breeding organisation (eight r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 15 publications
4
14
5
Order By: Relevance
“…Similarly, estimates of heritabilities for MTM-SPAR ranged from 0.04 ± 0.01 (first and second parity) to 0.09 ± 0.02 (third to last parity) for NBA, 0.06 ± 0.02 (second parity) to 0.08 ± 0.02 (third to last parity) for LTBW. The heritabilities estimated here for NBA and LTBW with MTM-PAR model were somewhat lower than those estimated in other countries (Oh et al, 2006;Fernández et al, 2008;Skorput et al, 2014). However, the estimates of heritability for NBA1 and NBA3+ in the MTM-SPAR were higher than those reported by Skorput et al (2014).…”
Section: Resultscontrasting
confidence: 76%
See 1 more Smart Citation
“…Similarly, estimates of heritabilities for MTM-SPAR ranged from 0.04 ± 0.01 (first and second parity) to 0.09 ± 0.02 (third to last parity) for NBA, 0.06 ± 0.02 (second parity) to 0.08 ± 0.02 (third to last parity) for LTBW. The heritabilities estimated here for NBA and LTBW with MTM-PAR model were somewhat lower than those estimated in other countries (Oh et al, 2006;Fernández et al, 2008;Skorput et al, 2014). However, the estimates of heritability for NBA1 and NBA3+ in the MTM-SPAR were higher than those reported by Skorput et al (2014).…”
Section: Resultscontrasting
confidence: 76%
“…The heritabilities estimated here for NBA and LTBW with MTM-PAR model were somewhat lower than those estimated in other countries (Oh et al, 2006;Fernández et al, 2008;Skorput et al, 2014). However, the estimates of heritability for NBA1 and NBA3+ in the MTM-SPAR were higher than those reported by Skorput et al (2014). The levels of genetic variation found in this commercial herd indicated that these traits would respond to genetic selection.…”
Section: Resultscontrasting
confidence: 68%
“…Petrovic et al, 2013), Black Slavonian(Skorput et al, 2014) and Nero di Parma(Menčik et al, 2017); only close to the Malhado de Alcobaça(Vicente, 2006), another Portuguese breed. Yet, values fall considerably lower when compared to exotic breeds used in intensive pig production systems(Nagyné-Kiszlinger et al, 2013;Krupa et al, 2016;Li et al, 2017;Lopez et al, 2017).…”
mentioning
confidence: 99%
“…Comparisons of different genetic index estimation methods for litter size are described by Skorput et al (2014). The objective of that study was to estimate genetic indices for litter size of the Black Slavonian pigs using the repeatability, multiple trait, and random regression models.…”
Section: Pigsmentioning
confidence: 99%